Edmond Halley's Reconstruction of the Lost Book of Apollonius's Conics Translation and Commentary - Fried, Michael N. (Sources and Studies in the History of Mathematics and Physical Sciences, 2012)
Apollonius's Conics was one of the greatest works of advanced mathematics in antiquity.  The work comprised eight books, four of which have come down to us in their original Greek and three in Arabic.  By the time the Arabic translations were produced, the eighth book had already been lost. In 1710, Edmond Halley, then Savilian Professor of Geometry at Oxford, produced an edition of the Greek text of the Conics of Books I-IV, a translation into Latin from the Arabic versions of Books V-VII, and a reconstruction of Book VIII.   Motivated by such questions as what role did Halley's reconstruction play in the mathematical world of the late 17th and early 18th century? and what did Halley see himself learning from engaging with mathematicians such as Apollonius?, Michael Fried's work provides the first complete English translation of Halley's reconstruction of Book VIII with supplementary notes on the text.  The volume also contains an introduction discussing aspects of Apollonius's Conics, an investigation of Edmond Halley's understanding of the nature of his venture into ancient mathematics, and appendices giving brief accounts of Apollonius's approach to conic sections and his mathematical techniques. This book will be of great interest to students and researchers interested in the history of ancient Greek mathematics and mathematics in the early modern period. .